Intrinsic flame-retardant solid-solid phase change material as well as preparation method and application thereof
The intrinsic flame retardant solid-solid phase change materials prepared with polyethylene glycol, epoxy resins and flame retardants are solved, and the problems of flammability and leakage of phase change materials are achieved, achieving efficient battery thermal management and service life.
Patent Information
- Application Number
- CN202411759095.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
Phase change materials are flammable and leak-prone in battery thermal management, resulting in increased thermal runaway and shortened service life.
A inherent flame retardant solid-solid phase change material is prepared using polyethylene glycol, epoxy resin and flame retardant (phosphorus pentoxide, expanded graphite and melamine). Through esterification reaction and curing molding technology, a material with flame retardant and thermal conductivity is formed.
This material is not easy to leak during the phase transition process, has good flame retardant and thermal conductivity, which can effectively improve the temperature consistency and structural stability of the battery module and extend the service life.
Smart Images

Figure CN119570227A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phase change materials, and in particular to an intrinsic flame retardant solid-solid phase change material and a preparation method and application thereof. Background Art
[0002] In order to cope with the energy crisis and environmental crisis worldwide, electric vehicles and hybrid vehicles have been vigorously developed in the field of transportation. With the transformation and development of the automobile industry, lithium-ion batteries have attracted widespread attention due to their advantages such as high energy density, low self-discharge rate and long life. However, lithium-ion batteries are temperature-sensitive components. During the operation of power batteries, the batteries will inevitably generate a lot of heat. The generation and accumulation of heat increases the operating temperature of power batteries and accelerates the aging of power battery performance. In order to match people's demand for the use of power vehicles, the energy density and fast charging and discharging technology of lithium batteries will continue to develop rapidly, and the heat generated by power batteries will also be further improved accordingly. Therefore, in order to make the battery work within the normal temperature range, the battery module needs to be effectively thermally managed. In recent years, the main cooling methods of battery modules are mainly divided into three types: air cooling, liquid cooling and phase change material cooling. However, air cooling and liquid cooling methods are difficult to meet the requirements of high integration and high energy density of electric vehicles. In contrast, phase change material cooling is widely used in thermal management systems because of its simple structure and can reduce the surface temperature of battery modules without consuming additional energy.
[0003] The basic principle of the phase change material cooling method is to absorb or release latent heat during the phase change process of the phase change material to reduce or increase the battery temperature, while maintaining the temperature consistency in the battery module to a certain extent. However, the application of phase change materials in battery thermal management is limited by their flammability and leakage. When a battery module has thermal runaway, the phase change material may cause the thermal runaway of the battery module to intensify due to its flammability, accelerating the rate of spread of thermal runaway. In addition, since traditional phase change materials use epoxy resin and styrene-butadiene rubber as the supporting skeleton, the material's anti-leakage performance in thermal stability depends on the amount of skeleton content, which greatly limits the optimization of other properties of phase change materials.
[0004] The traditional solution to the flammability and leakage of phase change materials is to add flame retardants to the phase change materials to give them flame retardant properties. At the same time, a larger proportion of supporting skeletons is added to the phase change materials to limit the flow of phase change components, so that the phase change materials have good anti-leakage properties. However, this method does not substantially change the solid-liquid phase change characteristics of the phase change material. After long-term and multi-cycle use, the problem of phase change material leakage is still inevitable, which greatly reduces the service life of the phase change material and even corrodes the battery module. In addition, the flame retardant may gradually become ineffective due to factors such as long-term friction and loss during use. Summary of the invention
[0005] The object of the present invention is to provide an intrinsic flame retardant solid-solid phase change material and a preparation method and application thereof, wherein the intrinsic flame retardant solid-solid phase change material can solve the technical problems of easy leakage and combustion of phase change materials.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides an intrinsic flame retardant solid-solid phase change material, which comprises the following raw materials by weight: 65-75 parts of polyethylene glycol, 7-17 parts of epoxy resin and 18-33 parts of flame retardant;
[0008] The flame retardant comprises phosphorus pentoxide, expanded graphite and melamine;
[0009] The epoxy resin includes epoxy resin glue and epoxy curing agent.
[0010] Preferably, the polyethylene glycol includes one or more of polyethylene glycol 1500, polyethylene glycol 2000, polyethylene glycol 4000 and polyethylene glycol 8000.
[0011] Preferably, the mass ratio of phosphorus pentoxide, expanded graphite and melamine is (2-3): (1-5): (15-25).
[0012] Preferably, the mass ratio of the epoxy resin glue to the epoxy curing resin is (0.95-1):(1-1.05).
[0013] The present invention also provides a method for preparing the intrinsic flame retardant solid-solid phase change material described in the above technical solution, comprising the following steps:
[0014] After polyethylene glycol is melted, it is mixed with phosphorus pentoxide and subjected to esterification reaction to obtain polyethylene glycol phosphate;
[0015] After the polyethylene glycol phosphate is melted, epoxy resin glue, expanded graphite, melamine and epoxy curing agent are added in sequence, and the mixture is cured and formed to obtain the intrinsic flame-retardant solid-solid phase change material.
[0016] Preferably, the esterification reaction temperature is 90-130°C and the time is 3-5h;
[0017] The esterification reaction is carried out under stirring conditions, and the stirring speed is 400-800 rpm.
[0018] Preferably, the process of sequentially adding epoxy resin glue, expanded graphite, melamine and epoxy curing agent comprises: sequentially adding epoxy resin glue, first stirring, adding expanded graphite, second stirring, adding melamine, third stirring, adding epoxy curing agent, and fourth stirring.
[0019] Preferably, the first stirring speed is 600-1000 rpm, and the time is 1-2 hours;
[0020] The second stirring temperature is 70-90°C, the rotation speed is 600-1000rpm, and the time is 1-2h;
[0021] The third stirring temperature is 70-90°C, the rotation speed is 800-1200rpm, and the time is 1-2h;
[0022] The temperature of the fourth stirring is 70-90° C., the rotation speed is 600-1000 rpm, and the time is 3-10 min.
[0023] Preferably, the addition rate of melamine is 30-50 g / min.
[0024] The present invention also provides the use of the intrinsic flame retardant solid-solid phase change material described in the above technical solution or the intrinsic flame retardant solid-solid phase change material prepared by the preparation method described in the above technical solution in a battery thermal management system.
[0025] The present invention provides an intrinsic flame retardant solid-solid phase change material, which includes the following raw materials by weight: 65-75 parts of polyethylene glycol, 7-17 parts of epoxy resin and 18-33 parts of flame retardant; the flame retardant includes phosphorus pentoxide, expanded graphite and melamine; the epoxy resin includes epoxy resin glue and epoxy curing agent. In the raw materials for preparing the intrinsic flame retardant solid-solid phase change material of the present invention, polyethylene glycol and phosphorus pentoxide can react to form polyethylene glycol phosphate, and the polyethylene glycol phosphate can stably graft melamine. The polyethylene glycol segment provides latent heat properties, and the access of phosphoric acid groups and melamine gives the phase change material flame retardant properties. At the same time, melamine makes the polyethylene glycol phosphate change the phase change properties, essentially changing the phase change morphology of the phase change component from solid-liquid phase change to solid-solid phase change, fundamentally solving the problem of easy leakage of the phase change material during the phase change process. And melamine can effectively improve the thermal conductivity of the phase change material and achieve rapid heat dissipation. The intrinsic solid-solid phase change material is made into a phase change material skeleton, and batteries can be loaded in the phase change material skeleton to form an integrated battery thermal management system, which greatly improves structural stability and resistance to external impact, while also improving thermal conductivity and effectively improving the temperature consistency of the battery pack. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1The XRD diagram of the intrinsic flame retardant solid-solid phase change material and polyethylene glycol described in Example 1;
[0027] Figure 2 This is a Fourier transform spectrum of the intrinsic flame retardant solid-solid phase change material and polyethylene glycol described in Example 1;
[0028] Figure 3 The anti-leakage test result of the intrinsic flame retardant solid-solid phase change material described in Example 2;
[0029] Figure 4 The vertical combustion test results of the intrinsic flame retardant solid-solid phase change material described in Example 2;
[0030] Figure 5 It is a structural schematic diagram of the battery module described in the application example;
[0031] Figure 6 A partial exploded view of the battery module described in the application example;
[0032] Figure 7 It is a schematic diagram of the top view of the structure of the phase change material skeleton and the battery in the battery module described in the application example;
[0033] Figure 8 This is a diagram of the thermal management test results in the battery module described in the application example;
[0034] Among them, 1 is the phase change material skeleton, 2 is the battery module, and 3 is the welding sheet. DETAILED DESCRIPTION
[0035] The present invention provides an intrinsic flame retardant solid-solid phase change material, which comprises the following raw materials by weight: 65-75 parts of polyethylene glycol, 7-17 parts of epoxy resin and 18-33 parts of flame retardant;
[0036] The flame retardant comprises phosphorus pentoxide, expanded graphite and melamine;
[0037] The epoxy resin includes epoxy resin glue and epoxy curing agent.
[0038] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0039] According to the mass percentage, the raw materials for preparing the intrinsic flame retardant solid-solid phase change material of the present invention include 65-75 parts of polyethylene glycol, preferably 68-72 parts, and more preferably 70 parts. In the present invention, the polyethylene glycol preferably includes one or more of polyethylene glycol 1500, polyethylene glycol 2000, polyethylene glycol 4000 and polyethylene glycol 8000. When the polyethylene glycol is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and can be mixed in any ratio. In the present invention, the polyethylene glycol provides latent heat properties.
[0040] Based on the mass fraction of the polyethylene glycol, the raw materials for preparing the intrinsic flame retardant solid-solid phase change material of the present invention include 7 to 17 parts of epoxy resin, preferably 8 to 15 parts, and more preferably 10 to 13 parts. In the present invention, the epoxy resin includes epoxy resin glue and epoxy curing agent; the epoxy resin glue is preferably Eric epoxy resin glue, and the epoxy curing agent is preferably Eric epoxy curing agent; the mass ratio of the epoxy resin glue and the epoxy curing agent is preferably (0.95 to 1): (1 to 1.05), more preferably 1: (1 to 1.05), and most preferably 1: 1.
[0041] In the present invention, the epoxy resin is a skeleton material.
[0042] Based on the mass fraction of the polyethylene glycol, the raw materials for preparing the intrinsic flame retardant solid-solid phase change material of the present invention include 18 to 33 parts of flame retardant; the flame retardant includes phosphorus pentoxide, expanded graphite and melamine; the mass ratio of phosphorus pentoxide, expanded graphite and melamine is preferably (2 to 3): (1 to 5): (15 to 25), more preferably (2.2 to 2.8): (2 to 4): (18 to 23), and most preferably (2.4 to 2.6): (2.3 to 2.6): (20 to 22).
[0043] In the present invention, the phosphorus pentoxide and melamine are intrinsic flame retardant components, and the expanded graphite is a thermal conductive filler, and the three work together to solve the problem of easy combustion; at the same time, the melamine further essentially changes the phase change form of the phase change component from solid-liquid phase change to solid-solid phase change, fundamentally solving the problem of easy leakage of the phase change material during the phase change process.
[0044] The present invention also provides a method for preparing the intrinsic flame retardant solid-solid phase change material described in the above technical solution, comprising the following steps:
[0045] After polyethylene glycol is melted, it is mixed with phosphorus pentoxide and subjected to esterification reaction to obtain polyethylene glycol phosphate;
[0046] After the polyethylene glycol phosphate is melted, epoxy resin glue, expanded graphite, melamine and epoxy curing agent are added in sequence, and the mixture is cured and formed to obtain the intrinsic flame-retardant solid-solid phase change material.
[0047] The invention melts polyethylene glycol, mixes it with phosphorus pentoxide, and performs esterification reaction to obtain polyethylene glycol phosphate.
[0048] The present invention has no special limitation on the melting process, and the melting process can be carried out by a process well known to those skilled in the art and ensure that the polyethylene glycol can be completely melted. In an embodiment of the present invention, the melting is specifically carried out in a magnetic stirring oil bath.
[0049] In the present invention, the process of mixing with phosphorus pentoxide preferably includes adding phosphorus pentoxide under stirring; the stirring speed is preferably 400-800 rpm, more preferably 600-800 rpm, and most preferably 600-700 rpm.
[0050] In the present invention, the temperature of the esterification reaction is preferably 90-130°C, more preferably 100-130°C, most preferably 120-130°C; the time of the esterification reaction is preferably 3-5h, more preferably 4-5h, most preferably 4.5-5h.
[0051] After obtaining polyethylene glycol phosphate, the present invention melts the polyethylene glycol phosphate, sequentially adds epoxy resin glue, expanded graphite, melamine and epoxy curing agent, and solidifies and shapes the polyethylene glycol phosphate to obtain the intrinsic flame-retardant solid-solid phase change material.
[0052] The present invention does not have any special limitation on the melting process, and the melting process can be carried out by a process well known to those skilled in the art. In an embodiment of the present invention, the melting is specifically carried out in an oil bath.
[0053] In the present invention, the process of sequentially adding epoxy resin glue, expanded graphite, melamine and epoxy curing agent preferably includes: sequentially adding epoxy resin glue, first stirring, adding expanded graphite, second stirring, adding melamine, third stirring, adding epoxy curing agent, and fourth stirring.
[0054] In the present invention, the rotation speed of the first stirring is preferably 600-1000rpm, more preferably 700-900rpm, and most preferably 700-800rpm; the time is preferably 1-2h, more preferably 1-1.5h, and most preferably 1-1.25h. In the present invention, the temperature of the second stirring is preferably 70-90°C, the rotation speed is preferably 600-1000rpm, more preferably 700-900rpm, and most preferably 700-800rpm; the time is preferably 1-2h, more preferably 1-1.5h, and most preferably 1-1.25h. In the present invention, the temperature of the third stirring is preferably 70-90°C, the rotation speed is preferably 800-1200rpm, more preferably 900-1200rpm, and most preferably 1000-1200rpm; the time is preferably 1-2h, more preferably 1-1.5h, and most preferably 1-1.25h. In the present invention, the temperature of the fourth stirring is preferably 70-90°C, the rotation speed is preferably 600-1000rpm, more preferably 700-900rpm, most preferably 700-800rpm; the time is preferably 3-10min, more preferably 4-8min, most preferably 5-6min. In the present invention, the addition rate of melamine is preferably 30-50g / min, more preferably 35-45g / min, most preferably 38-42g / min.
[0055] In the present invention, the addition rate of melamine can prevent the reaction between melamine and polyethylene glycol phosphate from being too fast, resulting in uneven mixing and destroying the continuity of the phase change material.
[0056] The present invention has no special limitation on the method of adding the epoxy resin glue, expanded graphite, melamine and epoxy curing agent, and they can be added in a method well known to those skilled in the art.
[0057] In the present invention, the curing molding is preferably carried out in a mold. The present invention does not have any special limitation on the mold, and the mold can be selected according to actual needs.
[0058] In the present invention, the curing temperature is preferably room temperature, and the curing time is preferably 3 to 5 hours, more preferably 4 to 5 hours, and most preferably 4.5 to 5 hours.
[0059] In the present invention, polyethylene glycol phosphate can stably graft melamine, polyethylene glycol segments provide latent heat properties, and the access of phosphoric acid groups and melamine gives the phase change material flame retardant properties. At the same time, melamine makes the polyethylene glycol phosphate change the phase change properties, essentially changing the phase change form of the phase change component from solid-liquid phase change to solid-solid phase change, fundamentally solving the problem of easy leakage of the phase change material during the phase change process. And the addition of melamine can effectively improve the thermal conductivity of the phase change material and achieve rapid heat dissipation.
[0060] The present invention also provides the use of the intrinsic flame retardant solid-solid phase change material described in the above technical solution or the intrinsic flame retardant solid-solid phase change material prepared by the preparation method described in the above technical solution in a battery thermal management system. The present invention does not have any special limitation on the method of the application, and the method well known to those skilled in the art can be used.
[0061] The intrinsic flame retardant solid-solid phase change material provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0062] Example 1
[0063] After 100 g of polyethylene glycol (specifically PEG2000) was completely melted in a magnetic stirring oil bath at 70° C., 3.55 g of phosphorus pentoxide was added under stirring (rotation speed was 600 rpm), the temperature of the magnetic stirring oil bath was set to 130° C., and stirring was performed for 3 h to obtain polyethylene glycol phosphate;
[0064] 100 g of the polyethylene glycol phosphate (all the polyethylene glycol phosphates prepared in the previous step) was placed in an oil bath and melted at 70° C., 4.93 g of epoxy resin glue (specifically, Eric epoxy resin glue) was added, and after stirring at 800 rpm for 1 hour, 2.82 g of expanded graphite was added, and after stirring at 800 rpm for 1 hour, 28.17 g of melamine (addition rate was 40 g / min) was added, and after stirring at 800 rpm for 1 hour, 4.93 g of epoxy curing agent (specifically, Eric epoxy curing agent) was added, and stirred at 1000 rpm for 7 minutes to obtain a mixture;
[0065] The mixture is poured into a mold and cured at room temperature for 5 hours to obtain the intrinsic flame retardant solid-solid phase change material.
[0066] Figure 1 is the XRD diagram of the intrinsic flame retardant solid-solid phase change material and polyethylene glycol, Figure 1 It can be seen that the intrinsic flame retardant solid-solid phase change material of the present invention has two diffraction peaks at 19.12° and 23.28°, which are the characteristic peaks of PEG. There are two diffraction peaks at 26.18° and 28.98° corresponding to the characteristic peaks of MA. Due to the introduction of MA, it can be observed that its peak becomes higher and higher, and the diffraction peak decreases to 19.12°, which may inhibit the crystallinity. It shows that the introduction of MA;
[0067] Figure 2 is the Fourier transform spectrum of the intrinsic flame retardant solid-solid phase change material and polyethylene glycol, Figure 2 It can be seen that the intrinsic flame retardant solid-solid phase change material of the present invention has a -1(CN, stretched), 1720cm -1 The characteristic peak at (C=O, stretching) is attributed to the side reaction, namely 2910 cm -1 (-CH2-, stretching) and 3400cm -1 The oxidation of the hydroxyl group at (-OH or -NH, stretching) indicates the successful incorporation of phosphorus pentoxide. -1 The FTIR spectrum showed a methylene absorption peak at , indicating that melamine reacted with polyethylene glycol phosphate.
[0068] Example 2
[0069] After 70 g of polyethylene glycol 2000 was completely melted in a magnetic stirring oil bath at 70° C., 3.3 g of phosphorus pentoxide was added under stirring (rotation speed was 600 rpm), the temperature of the magnetic stirring oil bath was set to 130° C., and stirring was carried out for 3 h to obtain polyethylene glycol phosphate;
[0070] 71 g of the polyethylene glycol phosphate (all the polyethylene glycol phosphates prepared in the previous step) was placed in an oil bath and melted at 70° C., 3.5 g of epoxy resin glue (specifically, Eric epoxy resin glue) was added, and stirred at 800 rpm for 1 h. 2 g of expanded graphite was added, and stirred at 800 rpm for 1 h. 20 g of melamine (addition rate was 800 rpm) was added, and stirred at 800 rpm for 1 h. 3.5 g of epoxy curing agent (specifically, Eric epoxy curing agent) was added, and stirred at 1000 rpm for 5 min to obtain a mixture;
[0071] The mixture is poured into a mold and cured at room temperature for 5 hours to obtain the intrinsic flame retardant solid-solid phase change material.
[0072] The intrinsic flame retardant solid-solid phase change material is subjected to a leakage test: the intrinsic flame retardant solid-solid phase change material is placed on a constant temperature heating table at 70°C, and the appearance and mass changes are observed and recorded at regular intervals. The mass change curve of the phase change material in the leakage test is used to characterize the thermal stability of the phase change material. The test results are as follows: Figure 3 As shown by Figure 3 It can be seen that the quality of the intrinsic flame retardant solid-solid phase change material in the anti-leakage test is almost unchanged, and the quality retention rate is still above 99% after continuous heating for more than 4 hours, which indicates that the anti-leakage performance of the intrinsic flame retardant solid-solid phase change material is greatly improved;
[0073] The intrinsic flame retardant solid-solid phase change material is subjected to a vertical combustion test: the vertical combustion test refers to the UL-94 test standard, and the intrinsic flame retardant solid-solid phase change material is subjected to two ignition tests. After the first ignition test, it is extinguished within 10 seconds, and after the second ignition, it is extinguished within 30 seconds, and there is no burning drop, which is the highest rating V0 level. The test results are as follows Figure 4 As shown by Figure 4 It can be seen that in the vertical combustion test, the intrinsic flame retardant solid-solid phase change material extinguished 1 second after the first ignition, and the burning material dripped and extinguished 6 seconds after the second ignition, but the dripping burning material did not cause the cotton to catch fire. Therefore, it can be proved that the flame retardant performance of the intrinsic flame retardant solid-solid phase change material is greatly improved compared with the traditional phase change material.
[0074] Example 3
[0075] After 700 g of polyethylene glycol 2000 was completely melted in a magnetic stirring oil bath at 70° C., 33 g of phosphorus pentoxide was added under vigorous stirring (rotation speed of 600 rpm), the temperature of the magnetic stirring oil bath was set to 130° C., and stirring was carried out for 3 h to obtain polyethylene glycol phosphate;
[0076] 710 g of the polyethylene glycol phosphate (all the polyethylene glycol phosphates prepared in the previous step) was placed in an oil bath pot and melted at 70° C., 35 g of epoxy resin glue (specifically, Eric epoxy resin glue) was added, and the mixture was stirred at 800 rpm for 1 h. 20 g of expanded graphite was added, and the mixture was stirred at 800 rpm for 1 h. 200 g of melamine (addition rate was 800 rpm) was added, and the mixture was stirred at 800 rpm for 1 h. 35 g of epoxy curing agent (specifically, Eric epoxy curing agent) was added, and the mixture was stirred at 1000 rpm for 5 min to obtain a mixture;
[0077] The mixture is poured into a mold and cured at room temperature for 5 hours to obtain the intrinsic flame retardant solid-solid phase change material.
[0078] The intrinsic flame-retardant solid-solid phase change material is assembled with a battery module (PPEM2-Module) for thermal management.
[0079] Example 4
[0080] After 700 g of polyethylene glycol 2000 was completely melted in a magnetic stirring oil bath at 70° C., 33 g of phosphorus pentoxide was added under vigorous stirring (rotation speed of 600 rpm), the temperature of the magnetic stirring oil bath was set to 130° C., and stirring was carried out for 3 h to obtain polyethylene glycol phosphate;
[0081] 710 g of the polyethylene glycol phosphate (all the polyethylene glycol phosphates prepared in the previous step) was placed in an oil bath pot and melted at 70° C., and then 85 g of epoxy resin glue (specifically, Eric epoxy resin glue) was added, and stirred at 800 rpm for 1 hour, and then 20 g of expanded graphite was added, and stirred at 800 rpm for 1 hour, and then 100 g of melamine (the addition rate was 800 rpm) was added, and stirred at 800 rpm for 1 hour, and then 85 g of epoxy curing agent (specifically, Eric epoxy curing agent) was added, and stirred at 1000 rpm for 5 min to obtain a mixture;
[0082] The mixture is poured into a mold and cured at room temperature for 5 hours to obtain the intrinsic flame retardant solid-solid phase change material.
[0083] The intrinsic flame retardant solid-solid phase change material is assembled with a battery module (PPEM-Module) for thermal management.
[0084] Comparative Example 1
[0085] 910 g of polyethylene glycol was placed in an oil bath and melted at 70° C., 35 g of epoxy resin glue (specifically, Eric epoxy resin glue) was added, and the mixture was stirred at 800 rpm for 1 h. 20 g of expanded graphite was added, and the mixture was stirred at 800 rpm for 1 h. 35 g of epoxy curing agent (specifically, Eric epoxy curing agent) was added, and the mixture was stirred at 1000 rpm for 5 min to obtain a mixture;
[0086] The mixture is poured into a mold and molded at room temperature for 5 hours to obtain the intrinsic flame retardant solid-solid phase change material.
[0087] The intrinsic flame retardant solid-solid phase change material is assembled with a battery module (PE-Module) for thermal management.
[0088] Application Examples
[0089] Battery module: Figures 5 to 7 As shown, it includes a skeleton 1 (wherein the skeleton 1 is the PE-Module described in Comparative Example 1, the PPEM2-Module described in Example 3, and the PPEM-Module described in Example 4), a battery module 2 and a welding sheet 3; the phase change material skeleton 1 is the same in size as the battery module 2 in height, both of which are 5 mm; the welding sheet 3 is a nickel sheet, and the battery module is welded in series and parallel. When the battery module 2 is loaded, the phase change material skeleton 1 is first tightly fitted to the battery module 2, and then the two are fixed, and finally the battery module is welded in series and parallel with the connecting sheet 3;
[0090] Figure 8is a graph of the thermal management test results in the battery module, wherein (a1) is the maximum temperature curve of the battery module cell of Comparative Example 1 in 10 charge and discharge cycles, (a2) is the temperature difference curve of the battery module cell of Comparative Example 1 in 10 charge and discharge cycles, (b1) is the maximum temperature curve of the battery module cell of Example 4 in 10 charge and discharge cycles, (b2) is the temperature difference curve of the battery module cell of Example 4 in 10 charge and discharge cycles, (c1) is the maximum temperature curve of the battery module cell of Example 3 in 10 charge and discharge cycles, and (c2) is the temperature difference curve of the battery module cell of Example 3 in 10 charge and discharge cycles; Figure 8 It can be seen that compared with Comparative Example 1, there is no phenomenon of continuous increase in the maximum temperature. The battery module composed of the intrinsic flame retardant material obviously has better battery module heat dissipation capacity, as well as better temperature uniformity performance and thermal management effect.
[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An intrinsic flame retardant solid-solid phase change material, characterized in that: The preparation material comprises the following raw materials by weight: 65-75 parts of polyethylene glycol, 7-17 parts of epoxy resin and 18-33 parts of flame retardant; The flame retardant comprises phosphorus pentoxide, expanded graphite and melamine; The epoxy resin includes epoxy resin glue and epoxy curing agent.
2. The intrinsic flame retardant solid-solid phase change material according to claim 1, characterized in that: The polyethylene glycol includes one or more of polyethylene glycol 1500, polyethylene glycol 2000, polyethylene glycol 4000 and polyethylene glycol 8000.
3. The intrinsic flame retardant solid-solid phase change material according to claim 1, characterized in that: The mass ratio of phosphorus pentoxide, expanded graphite and melamine is (2-3): (1-5): (15-25).
4. The intrinsic flame retardant solid-solid phase change material according to claim 1, characterized in that: The mass ratio of the epoxy resin glue to the epoxy curing resin is (0.95-1):(1-1.05).
5. The method for preparing the intrinsic flame retardant solid-solid phase change material according to any one of claims 1 to 4, characterized in that: The following steps are involved: After polyethylene glycol is melted, it is mixed with phosphorus pentoxide and subjected to esterification reaction to obtain polyethylene glycol phosphate; After the polyethylene glycol phosphate is melted, epoxy resin glue, expanded graphite, melamine and epoxy curing agent are added in sequence, and the mixture is cured and formed to obtain the intrinsic flame-retardant solid-solid phase change material.
6. The preparation method according to claim 5, characterized in that: The esterification reaction temperature is 90-130°C and the reaction time is 3-5h; The esterification reaction is carried out under stirring conditions, and the stirring speed is 400-800 rpm.
7. The preparation method according to claim 5, characterized in that: The process of sequentially adding epoxy resin glue, expanded graphite, melamine and epoxy curing agent includes: sequentially adding epoxy resin glue, first stirring, adding expanded graphite, second stirring, adding melamine, third stirring, adding epoxy curing agent, and fourth stirring.
8. The preparation method according to claim 7, characterized in that: The first stirring speed is 600-1000 rpm, and the time is 1-2 hours; The second stirring temperature is 70-90°C, the rotation speed is 600-1000rpm, and the time is 1-2h; The third stirring temperature is 70-90°C, the rotation speed is 800-1200rpm, and the time is 1-2h; The temperature of the fourth stirring is 70-90° C., the rotation speed is 600-1000 rpm, and the time is 3-10 min.
9. The preparation method according to claim 5, characterized in that: The addition rate of the melamine is 30-50 g / min.
10. Use of the intrinsic flame retardant solid-solid phase change material according to any one of claims 1 to 4 or the intrinsic flame retardant solid-solid phase change material prepared by the preparation method according to any one of claims 5 to 9 in a battery thermal management system.
Citation Information
Patent Citations
Temperature-control flame-retardant phase-change material for power lithium ion battery, preparation method of temperature-control flame-retardant phase-change material and lithium ion battery
CN114316910A
Flame-retardant composite material and preparation method thereof
CN118652533A
Flame-retardant phase-change material and preparation method thereof
CN118652534A
Cited By
Intrinsic flame-retardant epoxy resin-based composite phase change material and preparation method thereof
CN120248287A
Intrinsic flame-retardant solid-solid phase change material, preparation method thereof, battery module and application thereof
CN120888314A